ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Nugroho, Totok Susilo Pamuji (Riset Manajemen dan Akuntansi, 2023)
In this study, tax avoidance in manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange in 2019–2021 will be analyzed in relation to profitability, leverage, and sales growth. This research is quantitative. With 51 Manufacturing Companies in the Consumer Goods Industry Sector that are listed on the Indonesia Stock Exchange for the 2019–2021 period as the study population. then get a sample preferably 60 samples. Multiple linear regression analysis using the SPSS 25.0 program is the data analysis method used in this study. The results of this study indicate that the calculation of the hypothesis partially Profitability variable has a negative and partially insignificant effect on Tax Avoidance in consumer goods industry sector companies, Leverage has a positive and partially significant effect on Tax Avoidance in consumer goods industry sector companies, Sales Growth has a negative effect and partially insignificant to Tax Avoidance in companies in the consumer goods industry sector. The results of the study simultaneously variable Profitability, Leverage and sales growth do not have a significant effect on the Tax Avoidance variable. Keywords: Profitability, Leverage, Sales Growth, and Tax Avoidance